An improved atomizer with high output of nanoparticles. (October 2018) - Tang, Min; Chen, Sheng-Chieh; Pui, David Y.H.
Abstract: Filtration efficiency test of nanofibrous media requires particle generator to produce particles with small count median diameter (CMD) and high production rate. In EN 1822-5 standard, material recommended for particle generation is diethylhexylsebacyte (DEHS) due to its low volatility and stability. To obtain stable particle size and safe operation environment, it is preferred to use pure DEHS rather than solution with DEHS dissolved in solvent. In this work, two methods were used to reduce size of particles from pneumatic atomizer: mesh attachment and quick dilution. The results showed that the mesh can effectively reduce the CMD without compromising particle output, and quick dilution can significantly reduce the CMD with a higher particle output. By attaching mesh, the nozzle outlet with multiple holes can take advantage of smaller nozzle size while keeping enough airflow rate to draw the liquid. The quick dilution can greatly reduce the particle concentration right after spraying, and hence slow down the rate of particle coagulation. With mesh attached and dilution flow rate of 105 L/min, CMD of particles from improved atomizer was 104 nm, which was 56 nm smaller than that of original atomizer, and particle output was 6.30 × 10 12 #/min, which was 3 times higher than that of original atomizer. Highlights: Atomizer was improved by mesh attachment and quick dilution. The mesh can effectively reduce CMD without compromising particle output. Quick dilution can significantly reduce the CMD with a higher particle output.